Comparing galaxy populations in compact and loose groups of galaxies - Martínez, Héctor Julián; Coenda, Valeria; Muriel, Hernán (2021)
Abstract.We compare the properties of galaxies in compact groups, loose groups, and the eld to deepen our understanding of the physical mechanisms acting upon galaxy evolution in dierent environments. This contribution is detailed in Coenda et al. (2012) and Martínez et al. (2013).